Evaluation of the work of the Sharia Supervisory and Audit Board in Islamic banks - Sebaa, Fatma Zahra; Achouri, Hadda (The International tax journal, 2025)
The study aims at clarifying the nature of the work of the supervisory and auditing authority and the important role it plays in the transactions of Islamic banks and financial institutions, which gave it a distinguished personality from the traditional financial institutions (ribawiya), and we highlighted the most important objectives and tasks carried out by the supervisory board in Islamic banks. We tried to answer the problem of the study by clarifying the role of the Shari'a Supervisory Board in Islamic banks, in addition to pointing out some of the negatives directed at the work of the Commission.